X-ray changes in the stomach - intestinal motility in hypokinesia - Aliyev X. M; Umarova Z. M (Zien Journals, 2022)
In this article, gastrointestinal motility under condition of hypokinesia was studied during experiments. X-ray contrast examinations with barium sulfate showed that passage in the digestive tract slowed down due to changes in gastrointestinal evacuation activity under hypokinesia.
Keywords: hypokinesia; intestinal motility; X-ray contrast substance; stomach